Bioremediation of chromium(vi) to chromium(iii) - A. Rahim, Nur Izwinda (Department of Chemistry, UTM, 2016)
Wastewater discharged from industrial processes contains a lot of hazardous materials, of which Cr( VI) is categorized as carcinogenic and mutagenic, hence harmful towards human and living things. In this sense, industrial wastewater must be treated before discharged to the environment. Previous studies using mesophilic bacteria showed reduction of Cr(VI ) to Cr(III) in industrial effluents, but the strain could not survive at higher temperatures. Hence, reduction of Cr(VI) to Cr(III) by using thermophilic bacteria have been studied as this bacteria can withstand higher temperature. This study reports on the reduction of Cr(VI) to Cr(III) by Geobacillus caldoxylosilyticus UTM 6 (GenBank Acession No.KR867680) under optimized conditions. The effect of glucose (1000 ppm and 2000 ppm), sucrose (2000 ppm) and acetate (2000 ppm) on growth of G. caldoxylosilyticu s was studied. G. caldoxylosilyticus showed the highest growth in mixture of NB and glucose at concentration of 1000 ppm with OD 600 (0.817) compared to NB alone, OD 600 (0.798) after 13 h incubation. The maximum growth for G. caldoxylosilyticus in mixture o f salt minimal medium and glucose was at 8 h incubation with OD 600 of 0.079. G. caldoxylosilyticus shows the ability to utilize NH 4 + from basal salts with addition of glucose for metabolism. G. caldoxylosilyticus showed the highest reduction capacity of (9 2.79%) for 10 ppm Cr(VI) in mixture of NB and glucose after 24 h incubation compared to the control. G. caldoxylosilyticus was successfully shown to reduce Cr(VI) and can be used to treat Cr(VI) laden industrial effluent where the temperature may reach up to 60 ºC.